Frequency Reconfigurable Microstrip Patch Antenna for Multiband Applications with RF MEMS Shunt Capacitor Switch - Navarajan, J.; Jebarani, M. R. Ebenezar; Krishnan, V. Gokula (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The wireless communication systems are playing a significant role in the communication system. The requirement of wireless communication system is increased based on the day-by-day usage. The antenna is the most important device for the wireless communication and the necessity of designing the good antenna for the wireless communication system is increased. Therefore, the proposed work is developed a ultrawideband antenna with reconfiguring the frequency to enhance the performance of the antenna. Here, the frequency reconfigurable microstrip patch antenna is proposed and the frequency is tuned by utilizing RF MEMS shunt capacitor switch. The proposed antenna is designed with two reconfigurable switches and the antenna design is validated by three switching conditions such as ON-ON, ON-OFF, and OFF-OFF. The evaluation of the proposed frequency reconfigurable antenna is executed on the basis of antenna performance metrics such as Return loss, Bandwidth, Gain, Radiation pattern, and VSWR. The simulation results are demonstrating that the proposed frequency reconfigurable microstrip patch antenna with RF MEMS shunt capacitor switch is performed efficiently and this antenna is most suitable for the wireless communication system.